Effect of crude oil spot and futures price volatility on South East Asia Islamic equity market - Quadry, Mahmud Oluwaseyi; Adewale, Abideen Adeyemi; Jaiyeoba, Haruna Babatunde; Alli, Rafat Motunrayo (2016)
This paper examines the effect of crude oil price volatility on Southeast Asia Islamic equity market index. The paper focuses on the long run and short run effect of both the spot and futures price of crude oil on the Islamic equity market index in south East Asia. Daily data from September 2007 to June 2015 obtained from Bloomberg database is used in the paper. The analysis based on time series techniques within the co-integrating framework. The vector error correction model is used in this study complimented with Impulse Response Factor IRF to examine out of sample causality. The major finding of this study is that crude oil spot and futures prices have positive impact on the Islamic equity index in Malaysia, Singapore and Thailand. Though based on the short run relationship, there is remarkable difference in the speed of adjustment back to equilibrium among the Southeast Asia Islamic equity indices. Given the ongoing price volatility of crude oil prices and the market expectation that it may not abate anytime soon, this paper promotes the viability of the Southeast Asia Islamic equity market as investment safe haven to mitigate the impact of such volatility in crude oil prices.